Enhanced neuronal nitric oxide synthase expression is central to cardiac vagal phenotype in exercise-trained mice. - Danson, E; Paterson, D (2003)
We investigated whether enhanced cardiac vagal responsiveness elicited by exercise training is dependent on neuronal nitric oxide synthase (NOS-1), since the NO-cGMP pathway facilitates acetylcholine release. Isolated atria with intact right vagal innervation were taken from male mice (18-22 weeks old) after a period of 10 weeks voluntary wheel-running (+EX, n = 27; peaked 9.8 +/- 0.6 km day(-1) at 5 weeks), and from mice housed in cages without wheels (-EX, n = 27). Immunostaining of whole atria for NOS-1 identified intrinsic neurones, all of which co-localized with choline acetyltransferase-positive ganglia. Western blot analysis confirmed that NOS-1 protein level was significantly greater in +EX compared to -EX atria (P < 0.05, unpaired t test). Basal heart rates (HR) were slower in +EX than in -EX atria (322 +/- 6 versus 360 +/- 7 beats min(-1); P < 0.05, unpaired t test) However, in +EX atria, HR responses to vagal stimulation (VNS, 3 and 5 Hz) were significantly enhanced compared to -EX atria (3 Hz, +EX: -76 +/- 8 beats min(-1) versus -EX: -62 +/- 7 beats min(-1); 5 Hz, +EX: -106 +/- 4 beats min(-1) versus -EX: -93 +/- 3 beats min(-1); P < 0.01, unpaired t test). Inhibition of NOS-1 with vinyl-L-N-5-(1-imino-3-butenyl)-L-ornithine (L-VNIO, 100 microM) or soluble guanylyl cyclase with 1H-[1, 2, 4]oxadiazolo[4, 3-a]quinoxalin-1-one (ODQ, 10 microM) abolished the difference in HR responses to VNS between +EX and -EX atria, and effects of L-VNIO were reversed by excess L-arginine (1 mM; P < 0.01, ANOVA). There were no differences between the HR responses to the bath-applied acetylcholine analogue carbamylcholine chloride in +EX and -EX atria (IC(50) concentrations were 5.9 +/- 0.4 microM (-EX) and 5.7 +/- 0.4 microM (+EX)), suggesting that the changes in vagal responsiveness resulted from presynaptic facilitation of neurotransmission. In conclusion, NOS-1 appears to be a key protein in generating the cardiac vagal gain of function elicited by exercise training.